A quick and Sensitive Liquid Chromatography–Tandem Mass Spectrometry (LC-MS) Method for the Determination of Enalapril and Enalaprilat in Human Plasma: A pplication to a Bioequivalence Study: Enalapril and Enalaprilat assay in plasma - Hossein danafar; Mehrdad Hamidi (Iranian Journal of Pharmaceutical Sciences, 2016)
A rapid and sensitive liquid chromatography–tandem mass spectrometry (LC-MS) method was developed for the estimation of enalapril and enalaprilat in human plasma. Detection of analytes was achieved by tandem mass spectrometry with electrospray ionization (ESI) interface in positive ion mode was operated under the multiple-reaction monitoring mode. Sample pretreatment involved in a one-step protein precipitation (PPT) with percholoric acid (HClO4) of 0.15ml plasma. The reconstituted samples were chromatographed on C18 column by pumping methanol: water: acid formic74:24:2 (v/v) at a flow rate of 0.2 mL/min. Each plasma sample was chromatographed within 1.25 min. The standard curves were found to be linear in the range of 0.1–20 ng/mL for enalapril and enalaprilat with mean correlation coefficient of ≥0.999 for each analyte. The intra-day and inter-day precision and accuracy results were well within the acceptable limits. The limit of quantification (LOQ) was 0.1 ng/ml for enalapril and enalaprilat. The mean (SD) Cmax, Tmax, AUC0–tand AUC0–∞ values of enalapril versus enalaprilat after administration of the 10 mg enalapril are 141.33(3.51) versus73.33 (5.03) ng/mL, 1.15(1.45) versus 4.12 (1.74) hours, 142.57 (34.34) versus 425.94(13.09) ng/mL/h, and 150.74 (16.69) versus 455.80 (65.11) ng/mL/h respectively. The mean (SD) t1/2 was 2.72 (2.01) hours for the enalapril and 6.34 (2.13) hours for the enalaprilat. The developed assay method was successfully applied to a pharmacokinetic study in human male volunteers.